The Great Migration: Inception of the Zhou identity - Wu, Shu-hui (Studia Orientalia Electronica, 2011)
This essay explores the process of the accretion of the Zhou 周 people through migration, warfare, and intermarriage prior to the founding of the Western Zhou dynasty in 1045 BCE. It highlights two arguments: first, prior to the consolidation of the Zhou dynasty the Zhou ancestors had already laid the foundation of a unique Chinese cultural pattern for generations in the millennia to follow; and second, the Zhou people mostly consisted of the “Other”, namely the ethnic groups historians have called Rong Di 戎狄 and Qiang 羌 peoples, in addition to the Zhou ancestors, the descendants of the Yellow Emperor who, some six centuries before the Zhou took over the Shang dynasty, had migrated to the world of the “barbarians” and intermarried with them.